Xi Lei San Attenuates Dextran Sulfate Sodium-Induced Colitis in Rats and TNF-α-Stimulated Colitis in CACO2 Cells: Involvement of the NLRP3 Inflammasome and Autophagy - Zhang Tao; Xiaoqing Zhou; Yan Zhang; Wenfeng Pu; Yi Yang; Fuxia Wei; Qian Zhou; Lin Zhang; Zhonghan Du; Ji Wu (Hindawi Limited, 2021)
Objective. Inflammatory bowel disease (IBD) is a chronic nonspecific inflammatory bowel disease with an unclear etiology. The active ingredients of traditional Chinese medicines (TCMs) exert anti-inflammatory, antitumor, and immunomodulatory effects, and their multitarget characteristics provide them with a unique advantage for treating IBD. However, the therapeutic effects and underlying mechanisms of Xi Lei San in treatment of IBD remain unknown. This study was designed to investigate whether Xi Lei San exerted an anti-inflammatory effect in IBD via a mechanism involving NLRP3 inflammasomes and autophagy. Methods. We successfully established a rat model of dextran sulfate sodium- (DSS-) induced colitis as well as a cellular model of TNF-α-induced colitis. Xi Lei San and indirubin were identified by HPLC analysis. Rats were treated with Xi Lei San or alum crystals, and their body weights and morphology of intestinal tissues were examined. A western blot analysis was performed to determine the expression levels of inflammasome-related proteins and autophagy-related proteins, ELISA was performed to analyze IL-1β, IL-18, and IL-33 concentrations, and flow cytometry was used to monitor cell apoptosis and ROS levels. Results. Xi Lei San and indirubin were identified by HPLC analysis. We found that Xi Lei San could significantly increase the weights of rats and improve the structure of the intestinal tissues in DSS-induced colitis model rats. We also found that Xi Lei San significantly inhibited NLRP3 inflammasome activity, reduced the levels of inflammatory cytokines, and suppressed autophagy in DSS-induced colitis model rats. In vitro experiments revealed that Xi Lei San could repress apoptosis as well as ROS and inflammatory cytokine production in TNF-α-induced CACO2 cells by reducing the activity of NLRP3 inflammasomes and autophagy. Conclusions. Our findings showed that Xi Lei San significantly ameliorated IBD by inhibiting NLRP3 inflammasome, autophagy, and oxidative stress.